2000
DOI: 10.1074/jbc.m002101200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of a Novel Chondroitin 6-O-Sulfotransferase

Abstract: A novel human chondroitin 6-O-sulfotransferase, designated C6ST-2, was identified by BLAST analysis of expressed sequence tag using the sequence of a previously described human chondroitin 6-O-sulfotransferase (C6ST-1) as a probe. The new cDNA sequence revealed an open reading frame coding for a protein of 486 amino acids with a type II transmembrane protein topology. The amino acid sequence displayed 24% identity to the human C6ST-1, and the highest sequence identity was found in the COOH-terminal catalytic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 33 publications
3
66
1
1
Order By: Relevance
“…Signals of ⌬HexA-GalNAc(6S) and ⌬HexA(2S)-GalNAc(6S) were significantly reduced. The proportion of 6-O-sulfated disaccharide unit markedly decreased, but not to zero, which may be attributable to chondroitin 6-O-sulfotransferase 2 (19). Disaccharide composition analysis from urine revealed similar findings, with a strong reduction in the ⌬HexA-GalNAc(6S) and an increase in the nonsulfated unit (Table 5).…”
Section: Discussionsupporting
confidence: 65%
“…Signals of ⌬HexA-GalNAc(6S) and ⌬HexA(2S)-GalNAc(6S) were significantly reduced. The proportion of 6-O-sulfated disaccharide unit markedly decreased, but not to zero, which may be attributable to chondroitin 6-O-sulfotransferase 2 (19). Disaccharide composition analysis from urine revealed similar findings, with a strong reduction in the ⌬HexA-GalNAc(6S) and an increase in the nonsulfated unit (Table 5).…”
Section: Discussionsupporting
confidence: 65%
“…49) Disaccharide composition in urine is consistent with that in fibroblasts; specifically, the patient samples have some C and D units, but significantly fewer than control samples. 48) Thus, 6-O-sulfated CS formed by C6ST-1 plays critical roles in skeletal development and maintenance in humans.…”
Section: Human Chondrodysplasia Is Caused By Mutation In Chondroitin mentioning
confidence: 52%
“…Hiraoka et al (31) reported that the transcripts of C4ST-1 and C4ST-2, which produce CS-A, are also highly expressed in the small intestine, spleen, and leukocytes. In contrast, C6ST-2, which produces CS-C, is expressed significantly in the spleen, but not so in small intestine (34). The preference of CSGalNAcT-2 for CS-A and CS-B to CS-C and CS-D, as demonstrated in Table I, led us to speculate of a cooperative CS synthesis by CSGalNAcT-2 and C4STs in the cells.…”
Section: Discussionmentioning
confidence: 93%
“…Sulfation of chondroitin is important to exhibit various biological functions. Sulfation at position C-4 of GalNAc is directed by chondroitin-4-O-sulfotransferase-1 (C4ST-1) (30), C4ST-2 (31), and C4ST-3 (32), that at C-6 of GalNAc by chondroitin-6-O-sulfotransferase-1 (C6ST-1) (33) and C6ST-2 (34), and that at C-2 of GlcA by uronyl 2-sulfotransferase (35) in the GalNAc-GlcA backbone. It is still unclear whether the sulfation occurs after the synthesis of the long chondroitin chain or the sulfation and GalNAc-GlcA polymerization occur simultaneously.…”
Section: Discussionmentioning
confidence: 99%